الاستثمار الأجنبي المباشر، الموارد الطبيعية والنمو الاقتصادي في الجزائر -دراسةتحليلية قياسية - خلال الفترة 2000-2020 - عصماء رجم; كوثر طوايبية (My University, 2023)
Through this note, we tried to study the relationship between Foreign Direct Investment, Natural Resources and economic growth in Algeria from 2000 to 2020 (a standard analytical study using the EVIEWS 12 program), which required familiarization with various concepts and theories related to the subject, and after the theoretical and analytical study of statistics related to the study variables obtained from the World Bank website,we turned to the standard study using the time gap self-regression model (ARDL),We used GDP as a dependent variable reflecting economic growth, both FDI and natural resources as independent variables, where we found that there is an inverse relationship between FDI and GDP in Algeria,and between natural resources and GDP, with a direct(positive) relationship between FDI and natural resources, in addition to a long-term relationship between the variables of the study. .................................. من خلال هذه المذكرة حاولنا دراسة العلاقة بين الاستثمار الأجنبي المباشر، الموارد الطبيعية والنمو الاقتصادي في الجزائر من2000 إلى2020 (دراسة تحليلية قياسية باستخدام برنامج EVIEWS 12)، فتطلب ذلك التعرف على المفاهيم و النظريات المختلفة المتعلقة بالموضوع، وبعد الدراسة النظرية والتحليلية للإحصائيات المتعلقة بمتغيرات الدراسة والمتحصل عليها من موقع البنك العالمي، تطرقنا الى الدراسة القياسية باستخدام نمودج الانحدار الذاتي للفجوات الزمنية (ARDL)، وقد استخدمناالناتج المحلي الإجماليكمتغير تابع يعبر عن النمو الاقتصادي، كل من الاستثمار الأجنبي المباشر والموارد الطبيعية كمتغيرات مستقلة ، حيث توصلنا الى وجود علاقة عكسية بين كل من الاستثمار الأجنبي المباشر والناتج المحلي الإجمالي في الجزائر،و بين الموارد الطبيعية والناتج المحلي الاجمالي ، مع وجود علاقة طردية(موجبة) بين الاستثمار الأجنبي المباشر والموارد الطبيعية، إضافة الى وجود علاقة طويلة الأجل بين متغيرات الدراسة. .................................... À travers cette note, nous avons tenté d'étudier la relation entre les Investissements Directs Étrangers, les Ressources Naturelles et la croissance économique en Algérie de 2000 à 2020 (une étude analytique standard utilisant le programme EVIEWS 12), qui nécessitait une familiarisation avec divers concepts et théories liés au sujet, et après l'étude théorique et analytique des statistiques liées aux variables d'étude obtenues sur le site de la Banque mondiale, nous avons abordé l'étude standard utilisant les variables naturelles comme variables indépendantes, où nous arrivons à Il existe une relation inverse entre les IDE et le PIB en Algérie, et entre les ressources naturelles et le PIB, avec une relation directe(positive) entre les IDE et les ressources naturelles, en plus d'une relation à long terme entre les variables de l'étude.